All roads lead to you - Ashenden, Jackie (Sourcebooks Casablanca, 2022)
Finn Kelly guides hikes across the rugged wilderness he calls home. When jewelry designer Bethany Grant moves into town and proceeds to involve herself in every aspect of his life, he finds himself thinking he could use a friend. Bethany is drawn to dark, brooding Finn. She's an optimist and a fixer, but maybe Finn doesn't want to be fixed, and Bethany has her own grief to lay to rest. The question is how to come to terms with the darkness in your past in order to see the bright future that could lie ahead.